The theory and practice of modem design - Bingham, John A. C (Wiley, 1988)
Of related interest ... Digital Telephony John Bellamy "As a departure from conventional treatment of communication theory, the book stresses how systems operate and the rationale behind their design, rather than presenting rigorous analytical formulations." -Telecommunications Journal Both a reference for telecommunication engineers and a text for graduate level engineering and computer science students, this book provides an introduction to all aspects of digital communication, with emphasis on voice digitization, digital transmission, digital switching, network synchronization, network control, and network analysis. Its aim is to present system level design considerations, and then relate the specific equipment to telephone networks around the world, particularly North America. 526 pp. (0 471-08089-6) 1982 A Reference Manual for Telecommunications Engineering Roger L. Freeman Here's a comprehensive reference for those who design, build, purchase, use, or maintain telecommunications systems, offering the only system design database devoted exclusively to the field. It pulls together a vast amount of information from such diverse sources as CCITT/CCIR, EIA, US Military Standards and Handbooks, NBS, BTL/ATT, REA, and periodicals and monographs published by over twenty principal manufacturers. Covers telephone traffic, transmission factors in telephony, outside plant-metallic pair systems, noise and modulation, radio-frequency data and regulatory information, facsimile transmission, and more. 1504 pp. (0 471-86753-5) 1985